Sexual behaviours and sexual networks of men who have sex with men in Bali - Ni Luh Dea Kumala Sari Karang; Dewa Nyoman Wirawan; Anak Agung Sagung Sawitri (Universitas Udayana, 2017)
Background and purpose: Transmission of HIV and other sexually transmitted infections (STIs) among men who have sex with men (MSM) in Bali Province is increasing. This increased transmission is due to their sexual networks and behaviours. This study aims to examine sexual behaviours and sexual networks among MSM population in Bali Province. Methods: A descriptive cross-sectional study was conducted in Denpasar City and Badung District. A total of 130 MSM were recruited from Denpasar II Public Health Centre and Bali Medica Clinic – Badung District. Data were collected through interviews among MSM who visited both providers for STIs services from August to October 2015. Variables of this study included sociodemographic, sexual network (pattern and density), sexual activities in the last month, sexual role, condom/lubricant use, and history of previous STIs. Data were descriptively analysed. Results: As many as 53.1% respondents were aged <25 years, 90.8% were senior high school or higher degree graduates, 6.2% were married, 91.5% were employed, and 59.2% were having a regular partner. In the last month, as many as 70.8% respondents reported to have sex with first sexual partner, 52.3% with second sexual partners, and 45.6% with third sexual partners. Younger respondents tended to seek for younger sexual partners. The majority of respondents had had insertive sex, as many as 40.0% with their first partner, 44.6% with their second partner, and 43.2% with their third partner. About 20% of respondents were having high density sexual network and 71.5% of respondents were having concurrent sexual partnership. The consistent condom use within six months was 67.6% with the first partner, 72.8% with the second and the third partners. As many as 23% of respondents were diagnosed to have STIs. Conclusion: MSM population in Bali Province seem to have high risk sexual behaviours with great sexual network density, high concurrent sexual partnership, and selective mixing between older and younger MSM population.